Calendar Aging of Li-Ion Cells—Experimental Investigation and Empirical Correlation - Werner, Daniel; Paarmann, Sabine; Wetzel, Thomas (Batteries (Basel), 2021)
The lifetime of the battery significantly influences the acceptance of electric vehicles. Calendar aging contributes to the limited operating lifetime of lithium-ion batteries. Therefore, its consideration in addition to cyclical aging is essential to understand battery degradation. This study consequently examines the same graphite/NCA pouch cell that was the subject of previously published cyclic aging tests. The cells were aged at different temperatures and states of charge. The self-discharge was continuously monitored, and after each storage period, the remaining capacity and the impedance were measured. The focus of this publication is on the correlation of the measurements. An aging correlation is obtained that is valid for a wide range of temperatures and states of charge. The results show an accelerated capacity fade and impedance rise with increasing temperature, following the law of Arrhenius. However, the obtained data do also indicate that there is no path dependency, i.e., earlier periods at different temperature levels do not affect the present degradation rate. A large impact of the storage state of charge at 100% is evident, whereas the influence is small below 80%. Instead of the commonly applied square root of the time function, our results are in excellent agreement with an exponential function.